The limit and tensor product in the category of Q-P quantale modules. (3rd March 2016) - Liang, Shaohui
Abstract: In this paper, firstly, the definition of Q-P quantale modules and some relative concepts were introduced. we prove that the category of Q-P quantale modules is a pointed and connected category. Secondly, we give the structure of the limit of this category, so it is complete. At last, The definition of bimorphism of Q-P quantale modules is given. The tensor product of Q-P quantale modules is obtained, and some of their properties are discussed.